2014
DOI: 10.1080/14786419.2014.898146
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the phenolic compounds contributing to antibacterial activity in ethanol extracts of Brazilian red propolis

Abstract: The purpose of this study is to identify the quantity and antibacterial activity of the individual phenolic compounds in Brazilian red propolis. Quantitative analysis of the 12 phenolic compounds in Brazilian red propolis was carried out using reversed-phase high-performance liquid chromatography. The main phenolic compounds in Brazilian red propolis were found to be (3S)-vestitol (1), (3S)-neovestitol (2) and (6aS,11aS)-medicarpin (4) with quantities of 72.9, 66.9 and 30.8 mg g of ethanol extracts(- 1), respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 13 publications
5
35
0
3
Order By: Relevance
“…For example, isolated flavonoids such as 3',4'-dihydroxy-4-methoxydalbergione, 4-methoxydalbergion, cearoin, and chrysin (that are founded in species of Dalbergia) (Chan et al, 1998) inhibited the IL-33-induced mRNA expression of inflammatory genes including IL-6, TNF-α, and IL-13 in bone marrow-derived mast cells and the activation of NF-κB (Funakoshi-Tago et al, 2015). Other flavonoids such as medicarpin and isoliquiritigenin -which are also present in the Brazilian red propolis (Inui et al, 2014;Righi et al, 2011) -had no effect on the IL-33 signalling pathway or cytokine expression (Funakoshi-Tago et al, 2015).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…For example, isolated flavonoids such as 3',4'-dihydroxy-4-methoxydalbergione, 4-methoxydalbergion, cearoin, and chrysin (that are founded in species of Dalbergia) (Chan et al, 1998) inhibited the IL-33-induced mRNA expression of inflammatory genes including IL-6, TNF-α, and IL-13 in bone marrow-derived mast cells and the activation of NF-κB (Funakoshi-Tago et al, 2015). Other flavonoids such as medicarpin and isoliquiritigenin -which are also present in the Brazilian red propolis (Inui et al, 2014;Righi et al, 2011) -had no effect on the IL-33 signalling pathway or cytokine expression (Funakoshi-Tago et al, 2015).…”
Section: Figurementioning
confidence: 99%
“…quercetin (Alencar et al, 2007), pinocembrin, and biochanin A (Bueno- Silva et al, 2013;Inui et al, 2014;López et al, 2014;Righi et al, 2011). Between them, the flavonoid quercetin has been implied in neurogenic nociception -and in chronic painful peripheral neuropathy -through mechanisms that involve interactions with L-arginine-NO, serotonin, and GABAergic system (Azevedo et al, 2013;Filho et al, 2008).…”
Section: Figurementioning
confidence: 99%
“…The majority of propolis found around the world is derived from poplar buds; however, the most common type in Brazil, Brazilian green propolis from the southeastern part of the country, is derived from the buds of Baccharis dracunculifolia [3], and a recent our study reported that Brazilian red propolis from the northern part of the country is derived from Dalbergia ecastophyllum [4]. It appears highly likely that various types of propolis remain undiscovered around the world.…”
Section: Introductionmentioning
confidence: 88%
“…However, the precise amounts of phenolic compounds in Brazilian red propolis and their contributions to overall antibacterial activity have not been evaluated. Thus, we carried out the quantitative analysis and antibacterial evaluation of the phenolic compounds from Brazilian red propolis [4]. The main phenolic compounds in Brazilian red propolis were found to be (3S)-vestitol, (3S)-neovestitol, and (6aS,11aS)-medicarpin ( Figure 1).…”
Section: Brazilian Propolismentioning
confidence: 99%
“…Also, the medicarpin enriched acetone soluble fraction of the stem bark of Butea monosperma has been found to be more potent its total ethanolic extract OVx-induced bone loss [18] in rats, confirming the osteoprotective effect of medicarpin. Apart from its anti-osteoporotic property and its role in plant protection, a number of reports show that medicarpin elicits other remarkable therapeutic activities such asanti-cancer, anti-bacterial and neuroprotective [19][20][21] as well.…”
Section: Introductionmentioning
confidence: 99%